Crashtest: Immobilien und Wirtschaftskrisen. Eine Untersuchung der Immobilienmarktrenditen in Deutschland und den USA seit 1980 mit "Corona-Ausblick" - Jörn Oldenburg (IUBH Internationale Hochschule, 2020)
– In the long term, real estate in Germany and the USA delivers high returns of 5% to 8% per year. However, the path to these average yields differs greatly: total returns on the German real estate markets tend to develop similarly to the gross domestic product with only slight fluctuations. The US real estate markets tend to show high yield fluctuations with a time lag parallel to the stock market. The corona pandemic is a huge exogenous shock with an uncertain outcome for society, the economy and the financial markets. The study of real estate data over the last 40 years and the analysis of two economic crises (2000-2003 and 2007-2009) indicate that the German residential and office markets in particular will also survive the corona pandemic with stable performance. In the USA, stronger price declines are to be expected with a time lag, which will probably recover in subsequent years.
Keywords: R31; R33; O16; 650; Immobilien; Immobilienmarkt; Immobilienrenditen; Wirtschaftskrise; Finanzkrise; Corona